Re-examining Intercultural Competence in Mainland China through Actor-Network Theory - Ye, Yingying (Journal of intercultural communication, 2025)
This study advances a re-conceptualization of intercultural competence as an emergent, relational practice constituted within dynamic networks of interaction. Employing a conceptual methodology informed by Actor-Network Theory (ANT), it proposes a perspective that considers both human and non-human actors/actants, including technological artifacts, semiotic and linguistic resources, institutional structures, and spatial-material configurations- as integral to the production of intercultural agency and meaning. This perspective highlights how intercultural competence is enacted through networks and assemblages, emphasizing its distributed, performative, and contextually contingent nature. Rather than relying on essentialist, individual-centered paradigms that conceptualize competence as a stable attribute rooted in the accumulation of cultural knowledge and personal experience, which often reinforce static cultural categories and perpetuate stereotypes, this study employs ANT to shiftemphasis from the autonomous individual to the assemblages through which communicative agency is enacted. By destabilizing subject-centered assumptions, the proposed framework offers a more nuanced theoretical account attuned to the complexities of intercultural communication in increasingly hybrid, technologized, and interconnected environments.